Laparoscopic assisted repair of a giant bilateral congenital Morgagni hernia associated with malrotation in an infant - Maira Lazzarini; Mayara Padua Barbosa; Pedro Muñoz Fernandez (Elsevier, 2022)
Introduction: Morgagni hernia is a rare congenital malformation accounting for less than 5% of all congenital diaphragmatic hernias. Patients may be asymptomatic or present with non-specific respiratory or gastrointestinal symptoms, which can delay the diagnose. While it is highly associated with Down Syndrome, only a few series have reported association with malrotation. The defect can be unilateral or bilateral and colon is the most frequent herniated organ. Laparoscopic assisted repair seems to be the preferable approach for repairing the defect in the last years. Case report: We present a case of a 3-year-old Down Syndrome boy that was diagnosed with a giant Morgagni hernia while investigated for reflux disease. At the time of the surgery, he was found to have a bilateral defect with herniation of small bowel, omentum, cecum, appendix, ascending and transverse colon, as well as malrotation. The defects were successfully repaired with the laparoscopic assisted technique. Malrotation was corrected at the same time. Conclusion: Morgagni hernia is a rare congenital disease that can be associated with malrotation, which should always be investigated at the time of surgery. The laparoscopic assisted approach is an easy and safe way to repair the defect. Malrotation when present should be corrected at the same time.